The Influence of Innovation and Marketing Strategy on Consumer Purchasing Power in Markets in Dharmasraya Regency - Marlin, Revina; Rohim, Rika; Yenti, Yatna; Susanti, Tuti; Aima, M. Havidz (Journal of Science Education and Management Business, 2025)
This article examines the influence of innovation and marketing strategy on consumer purchasing power in the markets of Dharmasraya Regency. Using a quantitative approach, the research involved 30 randomly selected respondents from the local population. The findings indicate that while innovation is important for creating competitive advantages, it does not have a significant impact on consumer purchasing power. In contrast, marketing strategy has been shown to have a significant effect, suggesting that effective marketing approaches can enhance consumer experience and satisfaction. Consumer purchasing power is influenced by various factors, including economic conditions and community habits. These findings emphasize the importance of appropriate marketing strategies in enhancing purchasing power, while innovation must still be pursued to remain competitive in an increasingly tight market.